A dose-response study of nanosecond electric energy pulses on facial skin. (3rd July 2020) - Newman, James; Jauregui, Lauren; Knape, William A.; Ebbers, Edward; Uecker, Darrin; Mehregan, Darius; Nuccitelli, Richard
ABSTRACT: Nanosecond pulsed electric fields, also known as Nano-Pulse Stimulation or NPS, can trigger regulated cell death to clear skin lesions that are cellular in nature. Before treating facial lesions, it is important to demonstrate the effects of these pulses on normal facial skin. Here we have applied a range of NPS energies to the epidermis and dermis of normal facial skin scheduled for excision to establish a safe dose range of energies prior to use in clinical applications. This was an open-label, non-randomized study under the direction of a single Principal Investigator. The time course of the treated tissue changes was determined by histological analysis. All energy settings generated a delayed epidermal loss followed by re-epithelialization by day 7 and a normal course of healing. One day after NPS treatment, the cellular membranes of the treated epidermis were intact, but their nuclei no longer stained with H&E, resulting in a hollow appearance that has been referred to as "ghost cells." Cellular structures in the dermis, such as sebaceous glands and melanocytes, exhibited regulated cell death observed by 1 day post treatment. Melanocytes recovered to their normal density within 7 days. The 60-day samples indicated that epidermis, hair follicles, and eccrine glands appeared normal. The selective effect of NPS treatment on cellular structures in the epidermal and dermal layers suggests that this non-thermal modality of energy delivery is ideal for treating cellular targets including benign and malignant skin lesions. NPS skin treatments provide a promising method for clearing skin lesions with a cellular basis.